Drug-Resistant Epilepsy and Surgery - Sheng, Jiyao (Curr Neuropharmacol, 2018)
BACKGROUND: Epilepsy is a chronic brain disease that is caused by various factors and characterized by recurrent, episodic and temporary central nervous system dysfunction which results due to excessive discharge of brain neurons. In the past decades, despite the continuous development of antiepileptic drugs, there are still many patients with epilepsy progressing to drug-resistant epilepsy. Currently, surgical treatment is one of important way to cure drug-resistant epilepsy. METHODS: Data were collected from Web of Science, Medline, Pubmed, through searching of these keywords: “surgery” and “drug-resistant epilepsy”. RESULTS: An increasing number of studies have shown that surgery plays an important role in the treatment of drug-resistant epilepsy. Moreover, the comprehensive treatment mainly based on surgery can achieve the remission and even cure of drug-resistant epilepsy. CONCLUSION: In this review, we discuss the pathogenesis of drug-resistant epilepsy and the comprehensive treatment mainly based on surgery; this review may provide a reference for the clinical treatment of drug-resistant epilepsy.